Accumulation and spatial distribution of CO2 in the astronaut's crew quarters on the International Space Station. (November 2020) - Georgescu, Matei Razvan; Meslem, Amina; Nastase, Ilinca
Abstract: In poorly ventilated confined spaces, assessing the accumulation of CO2 in the breathing zone (BZ) is important evaluating human safety. The current study presents an experimental and numerical investigation of the CO2 generation rate and spatial distribution in the crew quarters (CQ) of the International Space Station. In microgravity, density-difference based airflow is nonexistent, and CO2 accumulates around the astronaut's head if the BZ is poorly or not at all ventilated. The aim is to study the breath's influence on CO2 spatial distribution in order to circumscribe the region that needs to be ventilated in the CQ. An experimental setup was used to measure the CO2 generation rate of several test subjects on Earth in a non-ventilated full-scale model of the CQ. The experimental CO2 results were used to validate CFD simulations of the CQ with gravity, with a human model inside featuring a full respiratory cycle. The validated CFD model was then used without gravity for a CO2 accumulation study. The respiratory cycle was analyzed in order to propose a rigorous definition of the BZ based on a frequency analysis of the breath. Results show that CO2 concentrations in the identified BZ are greater in the absence of gravity compared to a similar situation with gravity. It is believed that the ventilation system presently in place in the CQ does not effectively ventilate this strategic area, therefore a personalized ventilation type solution should be studied in the future. Highlights: Astronauts are at risk of CO2 intoxication in the confined environment they inhabit. An experimentally validated CFD model is used for analyzing CO2 accumulation. Fourier transforms of breath flow velocity can spatially delimit the breathing zone. In microgravity air is charged with more CO2 than a similar situation on Earth. Local ventilation of the breathing zone is necessary to disperse CO2 accumulation.